Granulomatous Features in Juvenile Idiopathic Arthritis-Associated Uveitis is Not a Rare Occurrence - Papasavvas I (Dove Medical Press, 2021)
Ioannis Papasavvas, Carl P Herbort Jr Retinal and Inflammatory Eye Diseases, Centre for Ophthalmic Specialized Care (COS), Clinic Montchoisi Teaching Centre, Lausanne, SwitzerlandCorrespondence: Carl P Herbort JrCentre for Ophthalmic Specialised Care, Montchoisi Teaching Centre, Rue Charles-Monnard 6, Lausanne, SwitzerlandEmail cph@herbortuveitis.chBackground: Juvenile idiopathic arthritis (JIA)-associated uveitis is the most common form of intraocular inflammation with systemic involvement in childhood. Textbooks tend to describe it as non-granulomatous anterior uveitis. Here, we report the percentage of granulomatous features in JIA-related uveitis among patients at a uveitis referral center.Methods: We conducted a retrospective study of all patients with JIA-related uveitis who were seen at the Center for Ophthalmic Specialized Care in Lausanne between 2000 and 2020. The sample comprised pediatric patients with bilateral anterior uveitis diagnosed as JIA-related with positive antinuclear antibody (ANA) titers. Exclusion criteria were a positive Mantoux or Quantiferon® test or elevated serum lysozyme and/or angiotensin converting enzyme (ACE) levels. The presence of one of the following features qualified the uveitis as granulomatous: granulomatous keratic precipitates (KPs) of mutton-fat type, smaller granulomatous KPs, or Koeppe nodules. The amount of inflammation was measured using laser flare photometry.Results: Thirty-eight patients were identified (mean age 13.34 ± 2.71 years; all female). In 12 patients (31.5%), the uveitis presented granulomatous features at presentation or during follow-up in at least one eye. Two of the 12 (16%) granulomatous patients had only light or no systemic involvement. The mean flare was 136.3± 149 ph/ms, which is much higher than granulomatous uveitis entities of other origin reported in the literature.Conclusion: JIA related uveitis can have a granulomatous presentation in about one third of patients with the Oligoarticular type and ANA positive, seen in a uveitis referral center. The presence of granulomatous features in bilateral uveitis in ANA-positive pediatric patients should not exclude the diagnosis of JIA-related uveitis, even in the absence of systemic involvement, as this entity presents a much more severe uveitis than other granulomatous anterior uveitis entities.Keywords: JIA-related uveitis, anterior uveitis, non-granulomatous anterior uveitis, granulomatous anterior uveitis, laser flare photometry